SKIN FROM THE POINT OF VIEW OF CHIKITSA AND KRIYA SHARIR - Dhimdhime, *R.S; Kodape, D.T; Pawar, K.B; Dhimdhime, S.R; Monika, Patwari (International Journal of Ayurveda and Pharma Research, 2017)
Skin is called â€œTwakâ€ which covers the whole body. Joseph Listre said â€œskin is the best dressingâ€; so a detail study of Twak is important, as it is the seat for all Twacha Rogas. The conceptual aspect of skin needs to be understood because skin disorder is outer exhibition of some kind of internal pathology. Skin, the largest organ of human body, holds significant importance in maintaining normal human physiological condition. The ancient science of Ayurveda has noted its features ages back. This article lays emphasis on the known and the lesser known functions of skin, its correlation with Ayurvedic science w.r.t the anatomical and physiological aspect. In depth analysis is provided regarding the thermoregulatory modality of skin. List of various clinically proven indigenous drugs of Ayurveda is also discussed briefly. Significance of skin as a tool to assess the health status of the patient is a boon of Ayurvedic diagnostic methodology; in detail description of which is provided in this article. This article is the simple and sincere attempt to explain the skin with a view of Kriya Sharir and Chikitsa.